Antiapoptotic Effects of EGb 761. (29th July 2013) - Serrano-García, Norma; Pedraza-Chaverri, José; Mares-Sámano, José Juan; Orozco-Ibarra, Marisol; Cruz-Salgado, Arturo; Jiménez-Anguiano, Anabel; Sotelo, Julio; Trejo-Solís, Cristina
Abstract : Ginkgo biloba extracts have long been used in Chinese traditional medicine for hundreds of years. The most significant extract obtained from Ginkgo biloba leaves has been EGb 761, a widely used phytopharmaceutical product in Europe. EGb 761 is a well-defined mixture of active compounds, which contains two main active substances: flavonoid glycosides (24–26%) and terpene lactones (6–8%). These compounds have shown antiapoptotic effects through the protection of mitochondrial membrane integrity, inhibition of mitochondrial cytochrome c release, enhancement of antiapoptotic protein transcription, and reduction of caspase transcription and DNA fragmentation. Other effects include the reduction of oxidative stress (which has been related to the occurrence of vascular, degenerative, and proliferative diseases), coupled to strong induction of phase II-detoxifying and cellular defense enzymes by Nrf2/ARE activation, in addition to the modulation of transcription factors, such as CREB, HIF-1 α, NF- κ B, AP-1, and p53, involved in the apoptosis process. This work reviews experimental results about the antiapoptotic effects induced by the standardized extract of Ginkgo biloba leaves (EGb 761).